Assessing Support Network Stability With Transition-Age Foster Youth: Measuring Change Over Time - Blakeslee, Jennifer E. (Res Soc Work Pract, 2016)
OBJECTIVE: This study uses the Support Network Assessment for Practice (SNAP) approach to measure the support provided to young people transitioning from foster care. METHODS: The SNAP was administered on two occasions, approximately 7 months apart, to a cohort of transition-age foster youth (n = 27). Analyses investigated measurement reliability and sensitivity to change for network-level characteristics as well as baseline factors associated with relationship stability. RESULTS: Most network-level indicators had strong test–retest correlations, and differences in mean scores over time also were detected, suggesting measurement sensitivity to change. Respondents were able to explain most observed changes in their networks, further suggesting reliable measurement. Stable relationships were those reported as stronger and providing more multifaceted support and those with family members and/or parent figures. DISCUSSION: The SNAP approach could be used to facilitate planning around support needs for youth transitioning out of foster care and to evaluate efforts to enhance support networks.